Multi-sensor filtering fusion with censored data under a constrained network environment - Geng, Hang; Wang, Zidong 1966-; Cheng, Yuhua (CRC Press, 2025)
"This book presents the up-to-date research developments and novel methodologies on Multi-Sensor filtering fusion (MSFF) for a class of complex systems subject to censored data under a constrained network environment. The contents of this book are divided into two parts covering centralized and distributed MSFF design methodologies. The work provides a framework of optimal centralized/distributed filter design and stability and performance analysis for the considered systems along with designed filters. Simulations presented in this book are implemented using MATLAB. The book includes concepts, backgrounds and models on censored data, filtering fusion and communication constraints and reviews case studies to provide clear engineering insights into the developed fusion theories and techniques. It provides theoretic values and engineering insights of the censored data and constrained network and discusses performance evaluation of the presented multi-sensor fusion algorithms. It also explores promising research directions on future multi-sensor fusion. This book is aimed at graduate students and researchers in networked control, sensor networks, and data fusion"--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on November 19, 2024)
Keywords: Sensor networks; Multisensor data fusion; Fusion multicapteurs; Réseaux de capteurs; TECHNOLOGY / Electricity